The Diagnostic Value of the Umbilical Cord Diameter Thickness in Second Trimester Congenital Anomaly Screening - Şenyuva, İrem and Taner, Cüneyt (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: Diagnostic value of the umbilical cord thickness second trimester congenital anomaly screening. STUDY DESIGN: Eighty-three pregnant women in the study. Patients were examined by dividing them into 3 groups. The first group was comprised of 50 healthy individuals which exhibited no chromosomal or sonographic fetal anomaly. The second group consisted of 8 cases which displayed chromosomal anomaly by amniocentesis. The third group included 25 cases with fetal anomaly detected by USG. RESULTS: The first group mean cord diameter was 7.06±1.6 mm (4.50-11.80 mm). Second group was 8.32±2.2 mm (4.60-11.0 mm), third group was 7.24±1.5 mm (4.70-10.50). No significant difference was determined between the results (p>0.05). CONCLUSION: Umbilical cord diameter was not found to be a valuable sonographic finding in the congenital anomaly screening.